2006
DOI: 10.1002/ps.1171
|View full text |Cite
|
Sign up to set email alerts
|

The effect of indoxacarb and five other insecticides on Phytoseiulus persimilis (Acari: Phytoseiidae), Amblyseius fallacis (Acari: Phytoseiidae) and nymphs of Orius insidiosus (Hemiptera: Anthocoridae)

Abstract: A laboratory study assessed the contact toxicity of indoxacarb, abamectin, endosulfan, insecticidal soap, S-kinoprene and dimethoate to Amblyseius fallacis (Garman), Phytoseiulus persimilis Athias-Henriot and nymphs of Orius insidiosus (Say). Amblyseius fallacis is a predacious phytoseiid mite and an integral part of integrated pest management (IPM) programmes in North American apple orchards. The other two beneficials are widely used in greenhouses to manage various arthropod pests infesting vegetable and orn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…Application of sublethal concentrations of abamectin on newly emerged females had an effect on the reproduction of these females and that of their progeny (Tables 2,5,6). Many studies have demonstrated the adverse effect of abamectin on fecundity of phytoseiid predators (Zhang and Sanderson 1990;Ibrahim and Yee 2000;Bostanian and Akalach 2006;Nadimi et al 2009). Sublethal concentration of abamectin also affected on fecundity of D. brevis (Uhler) (Kim et al 2006).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Application of sublethal concentrations of abamectin on newly emerged females had an effect on the reproduction of these females and that of their progeny (Tables 2,5,6). Many studies have demonstrated the adverse effect of abamectin on fecundity of phytoseiid predators (Zhang and Sanderson 1990;Ibrahim and Yee 2000;Bostanian and Akalach 2006;Nadimi et al 2009). Sublethal concentration of abamectin also affected on fecundity of D. brevis (Uhler) (Kim et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Abamectin had an adverse impact on reproduction of D. brevis (Kim et al 2006), P. plumifer (Nadimi et al 2009) and N. longispinosus (Ibrahim and Yee 2000). Some studies have examined the sublethal effects of abamectin on phytoseiid mites (Ibrahim and Yee 2000;Bostanian and Akalach 2006). Such data for effect of abamectin on P. plumifer has not been published yet.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Generally, natural enemies are usually more susceptible to the effects of pesticides than their plant-feeding hosts or prey owing to their generally smaller size, searching habits, and usually less-developed enzyme-based detoxification systems (Charlet, 1995). Bostanian and Akalach (2006) reported that the contact toxicity of dimethoate, abamectin and insecticidal soap to Amblyseius fallacis (Garman), Phytoseiulus persimilis Athias-Henriot and nymphs of Orius insidiosus (Say) was very toxic to all three beneficial adults. Kenneth et al (2002) reported the effects of acaricide residues on P. persimilis and T. urticae using a leaf disk system.…”
Section: Discussionmentioning
confidence: 98%
“…[78] [82] support the presumption that insect growth regulators (e.g., azadirachtin, buprofezin, kinoprene, and pyriproxyfen), in general, are not directly or indirectly harmful to either natural enemy under laboratory conditions. In addition, the insect growth regulators, cyromazine, diflubenzuron, and novaluron are not directly harmful to D. coriaria adults after 96 hours of exposure [28].…”
Section: Effects Of Pesticides On Dalotia Coriaria and Orius Insidiosusmentioning
confidence: 78%